Prevalence and factors associated with depression among clinically stable people living with HIV/AIDS on antiretroviral therapy - Sharanabasappa Algoodkar; Ajithkumar Kidangazhiathmana; P P Rejani; K S Shaji (Indian Journal of Psychological Medicine, 2017)
Background: Individuals with HIV/AIDS are prone for psychiatric/psychological morbidities. Many studies have reported significantly higher prevalence of depression in people living with HIV/AIDS (PLWHA's) when compared to general population. However, there are only very few studies looking at the prevalence of depression in patients on antiretroviral therapy (ART). Objectives: To estimate the prevalance and factors associated with depression among clinically stable PLWHAs. Materials and Methods: We used a cross-sectional study design to estimate the prevalence of depression and factors associated with it among clinically stable PLWHAs with CD4 cell count >400 cells/mm3 and on ART for >2 years. We assessed 100 PLWHAs and diagnosed depression using ICD-10 diagnostic criteria. Results: The prevalence of depression was 30% in this sample. Female gender, lack of family support, and HIV-positive status of the spouse were associated with depression in this study. Multiple logistic regression analysis showed lack of family support significantly associated with depression. High prevalence of depression and its association with stressful life circumstances even in individuals stable on ART points toward need for psychosocial interventions to improve metal health and well-being of these patients.